2013
DOI: 10.1007/s00244-013-9881-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Phytotoxicity of Seaport Sediments in the Framework of a Quarry-Deposit Scenario: Germination Tests of Sediments Aged Artificially by Column Leaching

Abstract: The aim of the Sustainable Management of Sediments Dredged in Seaports (SEDIGEST) project is to assess the risks of treated port sediments for terrestrial ecosystems when deposited in quarries. We simulated the "ageing" of these sediments up to the "moment" when plants can germinate. Sediments were leached by water percolating through a laboratory column. Sediments 1 and 2, taken from the port of Toulon (France), were dried and aired. Sediment 3, taken from the port of Guilvinec (France), was stabilised with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Plant species are recommended by the U.S. Environmental Protection Agency (EPA) and the Organization for Economic Cooperation and Development (OECD). Many earlier studies have demonstrated that white mustard (Sinapis alba L.) seeds are especially useful for toxicology tests [10][11][12]. The short germination period and fast growth of S. alba seeds are among the advantages of these tests.…”
mentioning
confidence: 99%
“…Plant species are recommended by the U.S. Environmental Protection Agency (EPA) and the Organization for Economic Cooperation and Development (OECD). Many earlier studies have demonstrated that white mustard (Sinapis alba L.) seeds are especially useful for toxicology tests [10][11][12]. The short germination period and fast growth of S. alba seeds are among the advantages of these tests.…”
mentioning
confidence: 99%